MEMO+: Efficacy, Durability and Effect of Cognitive Training and Psychosocial Intervention in Individuals with Mild Cognitive Impairment. Issue 4 (4th January 2018) - Belleville, Sylvie; Hudon, Carol; Bier, Nathalie; Brodeur, Catherine; Gilbert, Brigitte; Grenier, Sébastien; Ouellet, Marie‐Christine; Viscogliosi, Chantal; Gauthier, Serge
Abstract : Background/Objectives: There is no consensus on the efficacy of cognitive training in persons with mild cognitive impairment (MCI) because of the paucity of well‐designed randomized controlled trials. The objective was to assess the effect of memory training on the cognitive functioning of persons with MCI and its durability and to evaluate whether this effect generalizes to daily life and whether positive effects could be obtained from psychosocial intervention. Design: Single‐blind randomized controlled trial. Setting: Research centers of the Institut Universitaire de Gériatrie de Montréal and Institut Universitaire en Santé Mentale de Québec. Participants: Older adults meeting criteria for amnestic MCI (N = 145). Intervention: Participants were randomized to cognitive training, a psychosocial intervention, or a no‐contact control condition. Interventions were provided in small groups in eight 2‐hour sessions. Measurement: Outcome measures were immediate and delayed composite performance memory scores, psychological health (depression, anxiety, well‐being), and generalization effects of the intervention (strategy use in everyday life, difficulties in complex activities of daily living, memory complaints). Testing was administered before training and immediately, 3 months, and 6 months after training. Results: Participants in the cognitive training condition improved on the delayed composite memory score and on strategy use in everyday life. Improvement was maintained at the 3‐ and 6‐month follow‐up assessments. Participants in the psychosocial and no‐contact conditions did not show any significant improvement. Conclusion: Cognitive training improves the memory of persons with amnestic MCI. The effect persists over a 6‐month period, and learned strategies are used in everyday life. Cognitive training is a valid way to promote cognition in MCI. Abstract : See related editorial byRichard N. Jones .